THE TRACES OF ISLAMIC CULTURAL HISTORY: ANALYZING THE CULTURAL VALUES THAT INSPIRE INDONESIAN MUSLIMS - Abdul Wahab Syakhrani; Agus Fawait; Zainol Hasan; Antono Damayanto (ADISAM Publisher, 2024)
The article